Positive electrode and electrochemical device

By controlling the morphology of the lithium transition metal composite oxide and the orientation on the current collector surface, ensuring that its average particle size ratio in the positive electrode is within the range of 1.1≤Dp/Dv≤2.3, the problem of poor circulation performance caused by phase change and powdering during use of the positive electrode is solved, and the high-pressure circulation performance is improved and the stability guarantee is achieved.

CN115275099BActive Publication Date: 2025-04-18DONGGUAN AMPEREX TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210819420.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-12-24
Publication Date
2025-04-18
Estimated Expiration
2040-12-24

AI Technical Summary

Technical Problem

During the use of the existing positive electrode, due to the phase transition and powdering problems of lithium transition metal composite oxide, the circulation performance is poor.

Method used

By controlling the morphology of the lithium transition metal composite oxide and the orientation on the current collector surface, the average particle size ratio in the positive electrode is within the range of 1.1≤Dp/Dv≤2.3, thereby improving the ability to deintercalate lithium ions and the stability of the positive electrode.

Benefits of technology

The high-pressure cycling performance of the positive electrode is significantly improved, the performance degradation caused by phase transition and powdering is alleviated, and the crystallinity and cycling stability of lithium transition metal composite oxide are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275099B_ABST
    Figure CN115275099B_ABST
Patent Text Reader

Abstract

The present application provides a positive electrode, an electrochemical device and an electronic device. Among them, the positive electrode includes: a positive electrode active material layer located on a current collector, the positive electrode active material layer includes a lithium transition metal composite oxide, the average particle size of the lithium transition metal composite oxide in a direction parallel to the plane where the current collector is located is Dp, and the average particle size of the lithium transition metal composite oxide in a direction perpendicular to the plane where the current collector is located is Dv, satisfying 1.1≤Dp / Dv≤2.3. The inventors have found that by controlling the shape of the lithium transition metal composite oxide particles and regulating the orientation of their distribution on the surface of the current collector, the problems of pulverization and cracking of the lithium transition metal composite oxide during the use of the positive electrode (charging and discharging) can be alleviated, and the positive electrode has good high-voltage cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the following Chinese patent application: Application number 202080034071.7, application date December 24, 2020, invention name “Positive electrode and electrochemical device”. Technical Field

[0002] The present application relates to the field of battery technology, and more specifically, to positive electrodes and electrochemical devices. Background Art

[0003] With the development of new energy technologies and the progress of energy storage material research, secondary batteries such as lithium-ion batteries have been more widely used, and the market requirements for secondary battery performance have become increasingly stringent. The positive electrode is an important factor affecting the performance of secondary batteries, and the shape of lithium transition metal composite oxides has an important influence on the capacity and stability of the positive electrode.

[0004] Therefore, the current positive electrodes and secondary batteries still need to be improved. Summary of the invention

[0005] The present application aims to solve the technical problems in the related art at least to a certain extent. To this end, one purpose of the present application is to propose a positive electrode, which can improve the ability of the lithium transition metal composite oxide on the side in contact with the electrolyte to deintercalate lithium ions by controlling the morphology of the lithium transition metal composite oxide and the orientation of the lithium transition metal composite oxide on the surface of the current collector, and can improve the stability of the positive electrode, and alleviate problems such as pulverization caused by particle phase change.

[0006] In one aspect of the present application, the present application provides a positive electrode. The positive electrode includes: a positive electrode active material layer located on a current collector, the positive electrode active material layer includes a lithium transition metal composite oxide, the average particle size of the lithium transition metal composite oxide in a direction parallel to the plane where the current collector is located is Dp, and the average particle size of the lithium transition metal composite oxide in a direction perpendicular to the plane where the current collector is located is Dv, satisfying 1.1≤Dp / Dv≤2.3. The inventors have found that by controlling the shape of the lithium transition metal composite oxide particles and regulating the orientation of their distribution on the surface of the current collector, the problems of pulverization and cracking caused by the phase change and cracking of the lithium transition metal composite oxide during the use of the positive electrode (charging and discharging) can be alleviated, and the positive electrode has good high-voltage cycle performance.

[0007] According to some examples of the present application, the lithium transition metal composite oxide satisfies: 5μm≤Dp≤25μm. Therefore, the lithium transition metal composite oxide has a good orientation on the current collector, which can make the dominant crystal plane and the non-dominant crystal plane in the particles more reasonably arranged, so that the positive electrode can have better high-voltage cycle performance.

[0008] According to some examples of the present application, the lithium transition metal composite oxide satisfies: 0.8 ≤ (Dp + Dv) / 2D N50 ≤ 1.25, where D N50 is the median particle size of the lithium transition metal composite oxide.

[0009] According to some examples of the present application, the lithium transition metal composite oxide has an R-3m space group structure.

[0010] According to some examples of the present application, the lithium transition metal composite oxide includes Li x1 Ni y1 Co z1 Mn k Z q O b-a T a , where Z includes at least one of B, Mg, Al, Si, P, S, Ti, Cr, Fe, Cu, Zn, Ga, Y, Zr, Mo, Ag, W, In, Sn, Pb, Sb, and Ce, T is a halogen, and x1, y1, z1, k, q, a, and b respectively satisfy: 0.2 < x1 ≤ 1.2, 0 ≤ y1 ≤ 1, 0 ≤ z1 ≤ 1, 0 ≤ k ≤ 1, 0 ≤ q ≤ 1, 1 ≤ b ≤ 2, and 0 ≤ a ≤ 1.

[0011] According to some examples of the present application, the lithium transition metal composite oxide has a P63mc space group structure.

[0012] According to some examples of the present application, the lithium transition metal composite oxide includes Li x2 Na z2 Co 1-y2 M y2 O 2±n X n , where 0.6 < x2 < 0.95, 0 ≤ y2 < 0.15, 0 ≤ z2 < 0.03, 0 ≤ n ≤ 0.2, where M includes at least one of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr, and Zr, and X is a halogen.

[0013] According to some examples of the present application, in an electrochemical device including a positive electrode, when charged to a voltage of 4.6V, the positive electrode satisfies: the X-ray diffraction spectrum has at least characteristic peaks P1 and P2 in the range of 17° to 20°, and the peak intensity I1 of P1 is greater than the peak intensity I2 of P2.

[0014] According to some examples of the present application, when an electrochemical device including a positive electrode is discharged to a voltage of 3.0 V, the positive electrode satisfies: the X-ray diffraction spectrum has a characteristic peak P3 in the range of 17° to 20°. The peak intensity I3 of P3 satisfies: (I1-I2)≤I3≤(I1+I2). As a result, the positive electrode can have better cycle stability.

[0015] According to some examples of the present application, the ratio of the peak intensity I1 of P1 to the peak intensity I3 of P3 is not less than 0.8. Thus, the lithium transition metal composite oxide in the positive electrode can maintain good crystallinity during the cycle process.

[0016] According to some examples of the present application, the lithium transition metal composite oxide has a long axis average particle size D1 and a short axis average particle size D2, satisfying: 1.4≤(D1 / D2)≤5.5. According to some examples of the present application, the lithium transition metal composite oxide has a long axis average particle size D1 and a short axis average particle size D2, satisfying: 1.4≤(D1 / D2)≤3.8. As a result, the lithium transition metal composite oxide has a good particle morphology, and the ratio between active crystal planes and inactive crystal planes is moderate.

[0017] According to some examples of the present application, 7 μm≤D1≤28 μm.

[0018] According to some examples of the present application, the positive electrode satisfies: when the electrochemical device including the positive electrode is charged and discharged for 8 times in the range of 3.0V to 4.6V and discharged to a voltage of 3.0V, the peak position shift of the highest peak in the X-ray diffraction spectrum of the positive electrode after the cycle is no more than 0.1° compared with the positive electrode before the cycle; and the half-peak width change rate of the highest peak is less than 5%. Therefore, the positive electrode particles have good cycle performance.

[0019] In another aspect of the present application, the present application proposes an electrochemical device. The electrochemical device comprises: the aforementioned positive electrode, negative electrode, and separator. Thus, the secondary battery has all the characteristics and advantages of the aforementioned positive electrode, which will not be described in detail here.

[0020] According to an example of the present application, when the electrochemical device is discharged to a voltage of 3.0 V, the surface of the negative electrode has stripes.

[0021] In another aspect of the present application, the present application proposes a method for preparing the positive electrode described above. The method includes providing a lithium transition metal composite oxide, and configuring the lithium transition metal composite oxide, a conductive agent, and a binder to form a positive electrode slurry; coating the positive electrode slurry on the surface of the current collector; cold pressing the current collector with the positive electrode slurry, the cold pressing process is carried out at a pressure of 30-40 tons, the cold pressing rate is 3-4 meters / minute, and the compaction is controlled to be 4.05-4.25g / cm 3Thus, the aforementioned positive electrode can be easily obtained, and the positive electrode can have better cycle performance.

[0022] According to some examples of the present application, the weight ratio of lithium transition metal composite oxide to conductive agent and binder in the positive electrode slurry is (94-99): (0.5-3): (0.5-3). Thus, a positive electrode slurry with a proper ratio of conductive agent, lithium transition metal composite oxide and binder can be obtained.

[0023] According to some examples of the present application, after coating the positive electrode slurry on the surface of the current collector and before cold pressing, the method further includes drying the positive electrode slurry on the surface of the current collector; after the cold pressing, it further includes: cutting the current collector.

[0024] In another aspect of the present application, the present application provides a negative electrode modification method, which includes spreading an additive on the surface of the negative electrode active material layer and performing a roller pressing process, wherein the additive includes at least one of lithium powder, lithium ribbon and lithium-containing compound. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0026] Figure 1 is a schematic diagram of the structure of the positive electrode in an example of the present application;

[0027] Figure 2 is a schematic diagram of the structure of an electrochemical device in an example of the present application;

[0028] Figure 3 is a schematic flow chart of a method for preparing a positive electrode in an example of the present application;

[0029] Figure 4 is a scanning electron microscope photograph of the positive electrode in Example 1 of the present application;

[0030] Figure 5 is the X-ray diffraction spectrum of the positive electrode in Example 1 of the present application;

[0031] Figure 6 is the X-ray diffraction spectrum of the positive electrode in Comparative Example 1 of the present application;

[0032] Figure 7 is an optical photograph of the negative electrode in Example 1 of the present application;

[0033] Figure 8 is an optical photograph of the negative electrode in Comparative Example 1 of the present application;

[0034] Fig. 9 It is a graph of the cycle performance test results of Example 1 and Comparative Example 1 of the present application.

[0035] Description of reference numerals:

[0036] 100: positive electrode; 110: current collector; 120A-120C: lithium transition metal composite oxide; 120: active material layer; 200: separator; 300: negative electrode; 1000: electrochemical device. DETAILED DESCRIPTION

[0037] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0038] This application is completed based on the following knowledge and findings of the inventors:

[0039] Although the current positive electrode, such as the positive electrode of a lithium-ion secondary battery, can control the performance of the positive electrode by controlling the particle size and morphology of the active Li-containing material in the lithium transition metal composite oxide, the current positive electrode still has the problem that the cycle performance needs to be improved. The inventor found that in addition to the morphological characteristics of the lithium transition metal composite oxide itself, the orientation of the lithium transition metal composite oxide on the current collector will also affect the performance of the positive electrode. In particular, lithium transition metal composite oxides are usually not perfectly symmetrical spherical particles. The shape of the positive electrode material is limited by the growth control of its crystal face. The dominant crystal face in the particle will grow faster, while other crystal faces are slower. Therefore, lithium transition metal composite oxides are ellipsoidal rather than perfect spherical in most cases. When the synthesis conditions are regulated, the proportion of the crystal faces of the obtained lithium transition metal composite oxide will also change. For example, when there are too many dominant crystal faces in the lithium transition metal composite oxide, the long side of the ellipsoid of the obtained lithium transition metal composite oxide is much larger than the short side; and by controlling the reduction of the proportion of the dominant crystal face and increasing other crystal faces, particles close to spherical can be obtained. For cobalt-based materials, such as lithium cobalt oxide, the dominant surface cannot deintercalate lithium but is very stable, while the crystal plane with the largest proportion among the non-dominant surfaces, such as the 104 crystal plane, can deintercalate lithium but is unstable and prone to phase change. Therefore, when there are too many dominant surfaces, the delithiation of the material is affected, and the shape is too flat and difficult to process; conversely, when there are too many non-dominant surfaces, the particle surface is unstable and prone to phase change and failure. When forming the positive electrode, lithium transition metal composite oxides and conductive particles, binders and other components are generally configured into a slurry, and then the slurry is coated on the surface of the positive electrode current collector. After a series of treatments such as drying and cold pressing, the lithium transition metal composite oxide will be distributed on the surface of the current collector in a certain orientation.

[0040] Since lithium transition metal composite oxides are not symmetrical particles, if the orientation of the lithium transition metal composite oxides on the current collector is not controlled, the performance of the lithium transition metal composite oxides cannot be fully exerted. For example, when the dominant surface is exposed too much on the side of the current collector facing the electrolyte, although the stability of the positive electrode is good, the distance between the non-dominant surface and the electrolyte increases, and the performance of the positive electrode in lithium extraction will be affected. When the non-dominant surface is exposed too much on the side of the current collector facing the electrolyte, the stability of the positive electrode is poor, and the positive electrode material is prone to pulverization. In addition, if the lithium transition metal composite oxide is damaged during processing, or is unevenly distributed on the surface of the positive electrode current collector, and the orientation is chaotic, it is not conducive to the electrochemical performance of the lithium transition metal composite oxide.

[0041] In view of this, in one aspect of the present application, the present application provides a positive electrode. Figure 1 The positive electrode 100 includes a current collector 110 and an active material layer 120, the active material layer 120 is located on the current collector 110, and the active material layer 120 includes lithium transition metal composite oxides 120A, 120B, and 120C. The average particle size Dp of the lithium transition metal composite oxides 120A, 120B, and 120C in the direction parallel to the plane where the current collector 110 is located (the A-A' direction shown in the figure) and the average particle size Dv in the direction perpendicular to the plane where the current collector 110 is located (the B-B' direction shown in the figure) The ratio Dp / Dv satisfies 1.1≤Dp / Dv≤2.3. The inventors have found that the positive electrode has good high-voltage cycle performance. By controlling the shape of the lithium transition metal composite oxide particles and regulating the orientation of their distribution on the surface of the current collector, the positive electrode can alleviate the problems of pulverization caused by phase change and cracking of the lithium transition metal composite oxide during use (charging and discharging).

[0042] As mentioned above, since the lithium transition metal composite oxide is distributed in a certain orientation during the distribution process in the current collector, controlling the ratio of Dp and Dv of the lithium transition metal composite oxide can better measure the distribution of the lithium transition metal composite oxide on the surface of the current collector, thereby ensuring that the electrochemical performance of the lithium transition metal composite oxide can be well reflected at the positive electrode level. Specifically, generally for ellipsoidal or flat particles, if the lithium transition metal composite oxide is mostly distributed with the major axis diameter of the particles parallel to the plane where the current collector 110 is located (such as Figure 1120B shown in the figure), then the inactive surface is facing the negative electrode of the battery, and the migration path of lithium increases. In this state, the stability of the particles is good and it is not easy to pulverize. If the lithium transition metal composite oxide is mostly distributed in a state where the major axis diameter is perpendicular to the current collector 110, such as 120A shown in the figure, then the active surface is facing the negative electrode of the battery, which is easy to be damaged during the processing process, affecting the performance of the positive electrode. By controlling the particle morphology of the lithium transition metal composite oxide itself and regulating the processing process, such as but not limited to the pressure and pressure direction of cold pressing, the ratio of Dp and Dv can be guaranteed to be within a certain range, that is, at this time, the lithium transition metal composite oxide has enough non-dominant surfaces facing the negative electrode of the battery, which can make the positive electrode have better electrochemical performance, and at the same time, it will not be due to the excessive exposure of the dominant surface to the electrolyte side, resulting in poor cycle performance.

[0043] According to some examples of the present application, when Dp / Dv is within the range of 1.1-2.3, it can be ensured that the positive electrode material particles are distributed more evenly on the current collector 110, and at this time, the active surface and the inactive surface of the lithium transition metal composite oxide in the direction facing the negative electrode of the battery are within a reasonable range and can be maintained after processing. When Dp / Dv is less than 1.1, there are too few inactive crystal faces in the positive electrode facing the negative electrode of the battery, and the lithium transition metal composite oxide is easily damaged and pulverized; when Dp / Dv is greater than 2.3, the lithium transition metal composite oxide on the surface of the positive electrode is too flat or over-pressured, affecting the electrochemical performance of the positive electrode.

[0044] It should be noted here that, unless otherwise specified in this application, the average particle size is the average diameter of the particles. The average diameter is tested by randomly selecting one position of the positive electrode and processing it with a slicer to obtain a cross section. The diameters of the particles in the cross section are measured in parallel and vertical directions and the sizes are recorded. The diameter refers to the maximum length of the particles in the defined direction. The statistical method is to select particles from left to right and from top to bottom, and the statistical number of the average particle size is 100 particles. Figure 1 The Dp of the inclined lithium transition metal composite oxide 120C shown in FIG. 1 is the cross section of the particle at the positive electrode (eg Figure 1 Dv of the lithium transition metal composite oxide 120C is the maximum value of the length of the particle along the AA' direction at the viewing angle shown in FIG. 1 , and Dv of the lithium transition metal composite oxide 120C is the maximum value of the length of the particle along the BB' direction.

[0045] According to some examples of the present application, the lithium transition metal composite oxide has a long axis average particle size D1 and a short axis average particle size D2, which satisfy: 1.4≤(D1 / D2)≤5.5. According to some examples of the present application, 1.4≤(D1 / D2)≤3.8. As a result, the lithium transition metal composite oxide has a good particle morphology, and the ratio between active crystal planes and inactive crystal planes is moderate.

[0046] According to some specific examples of the present application, the average long axis particle size D1 satisfies: 7 μm≤D1≤28 μm. Therefore, the lithium transition metal composite oxide has a good particle morphology, and the ratio between active crystal planes and inactive crystal planes is moderate.

[0047] According to some examples of the present application, the lithium transition metal composite oxide can also satisfy: 5μm≤Dp≤25μm. Thus, the lithium transition metal composite oxide can have a better orientation on the current collector, and can arrange the dominant crystal planes and non-dominant crystal planes in the particles more reasonably, so that the positive electrode can have better high-voltage cycle performance.

[0048] According to some examples of the present application, the lithium transition metal composite oxide may further satisfy: 0.8≤(Dp+Dv) / 2D N50 ≤1.25. Where D N50 is the median particle size of the lithium transition metal composite oxide. It is understood by those skilled in the art that the particle sizes of general cobalt-based positive electrode materials are not completely consistent, and the lithium transition metal composite oxide in the positive electrode may contain large particles, small particles, or a mixture of large and small particles. However, its particle size may be within a certain range. N50 That is, the average particle size of the median size particles. N50 The relationship between Dp and Dv can determine whether the shape characteristics of the particle design of the lithium transition metal composite oxide are retained during the processing. Specifically, when the value of Dp + Dv is much greater than or less than 2D N50 When (Dp+Dv) / 2D N50 When it is between 0.8 and 1.25, it can be ensured that the lithium transition metal composite oxide is not damaged during processing, or the degree of damage is not enough to seriously affect the performance of the obtained positive electrode, and the lithium transition metal composite oxide can be distributed more evenly on the surface of the current collector in a certain orientation.

[0049] According to some examples of the present application, the specific chemical composition and structure of the lithium transition metal composite oxide are not particularly limited, and those skilled in the art can select according to the actual battery performance requirements. For example, according to some examples of the present application, the lithium transition metal composite oxide has a R-3m space group structure. According to some examples of the present application, the chemical composition of the lithium transition metal composite oxide can be Li x1 Ni y1 Co z1 Mn k Z q O b-a T a , where Z includes at least one of B, Mg, Al, Si, P, S, Ti, Cr, Fe, Cu, Zn, Ga, Y, Zr, Mo, Ag, W, In, Sn, Pb, Sb, and Ce, T is a halogen, and x1, y1, z1, k, q, a, and b respectively satisfy: 0.2 < x1 ≤ 1.2, 0 ≤ y1 ≤ 1, 0 ≤ z1 ≤ 1, 0 ≤ k ≤ 1, 0 ≤ q ≤ 1, 1 ≤ b ≤ 2, and 0 ≤ a ≤ 1. According to some examples of the present application, the lithium transition metal composite oxide has a P63mc space group structure. According to some examples of the present application, the chemical composition of the lithium transition metal composite oxide can be Li x2 Na z2 Co 1-y2 M y2 O 2±n X n , where 0.6 < x2 < 0.95, 0 ≤ y2 < 0.15, 0 ≤ z2 < 0.03, 0 ≤ n ≤ 0.2, where M includes at least one of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr, and Zr. For example, the number of types of M elements can be 1, 2, or 3 or more. When there are multiple M elements, y is the sum of the atomic ratios of the multiple M elements. More specifically, for Li x2 Na z2 Co 1-y2 M y2 O 2±n X n , x can satisfy 0.6 < x < 0.85.

[0050] According to some examples of the present application, when the electrochemical device including the positive electrode is discharged to a voltage of 3.0V, the X-ray diffraction spectrum of the lithium transition metal composite oxide has a characteristic peak P3 in the range of 17° to 20°. And when the electrochemical device including the positive electrode is charged to 4.6V, it will present two phases, the lithium content of the two phases is different, and the part with lower lithium content accounts for a larger proportion, that is, when the battery cell with the positive electrode is charged to a voltage of 4.6V, the X-ray diffraction spectrum has at least characteristic peaks P1 and P2 in the range of 17° to 20°, and the peak intensity I1 of P1 is greater than the peak intensity I2 of P2. As mentioned above, the crystallinity determines the material properties. The better the crystallinity, the less likely the material is to pulverize and the better the cycle stability. Specifically, the ratio I1 / I3 of the peak intensity I1 of P1 and the peak intensity I3 of P3 is not less than 0.8. That is to say, its crystallinity is reflected in the peak intensity I1 being in a close range compared to the initial peak intensity I3. If its intensity is lower than 0.8 of I3, it indicates that the crystallinity of the material has decreased significantly. When discharged to 3.0V, the lithium transition metal composite oxide returns to its initial state. If the material is strained and cracked at this time, I3 will be lower than I1-I2. However, if the initial peak intensity exceeds I1+I2, it indicates that there is a risk of pulverization at high voltage. Specifically, pulverization refers to the process of decreased crystallinity of lithium transition metal composite oxides such as cracking, degradation, and phase change. Therefore, the peak intensity I3 of P3 satisfies: (I1-I2)≤I3≤(I1+I2), which can make the positive electrode have better crystallinity and better cycle performance.

[0051] According to some examples of the present application, after the electrochemical device is fully charged and discharged to 3.0V, the surface of the negative electrode has stripes parallel to the fold direction. The stripes originate from the traces left after the additives in the negative electrode are consumed. As a result, the lithium transition metal composite oxide in the positive electrode cooperates with the structure of the negative electrode (such as additives) to have a more stable cycle performance, thereby allowing the charge and discharge state structure of the positive electrode active material of the positive electrode to remain stable during its application, that is, the crystal structure of the material changes little, that is, I1, I2 and I3 are more stable. In addition, after it is fully discharged to the initial state, the offset and broadening of its I3 peak are very small. Normally, the offset of the XRD characteristic peak means the loss of active lithium, and the broadening means the pulverization of the material.

[0052] According to the positive electrode of the present application, the electrochemical device including the positive electrode can be charged and discharged for 10 times in the range of 3.0V to 4.6V, and when the voltage is discharged to 3.0V, the peak position offset of the highest peak in the X-ray diffraction spectrum is not more than 0.1°, and the half-peak width change rate of the highest peak is less than 5%. It can be seen that the positive electrode proposed in the present application has good stability, and the active lithium loss during the use of the material and the pulverization of the positive electrode active material (lithium transition metal composite oxide) are less.

[0053] In another aspect of the present application, the present application provides an electrochemical device. Figure 2 The electrochemical device 1000 includes a positive electrode 100, a separator 200 and a negative electrode 300. The positive electrode 100 is as described above, and the separator 200 separates the positive electrode 100 and the negative electrode 300. Therefore, the electrochemical device has all the characteristics and advantages of the positive electrode described above, which will not be repeated here. In general, the electrochemical device has good cycle performance and capacity.

[0054] Those skilled in the art will appreciate that the electrochemical device may also include an electrolyte to achieve the functions of the electrochemical device. The specific shape of the electrochemical device is not particularly limited, and those skilled in the art may select and design it according to actual needs.

[0055] In another aspect of the present application, the present application provides a method for preparing the positive electrode described above. Figure 3 , the method may include:

[0056] S100: Providing positive electrode material and forming positive electrode slurry

[0057] According to some examples of the present application, this step may include providing a lithium transition metal composite oxide and forming a positive electrode slurry. Specifically, the lithium transition metal composite oxide, a conductive agent, and a binder may be configured to form a positive electrode slurry.

[0058] According to some examples of the present application, the weight ratio of lithium transition metal composite oxide to conductive agent and binder in the positive electrode slurry can be (94-99): (0.5-3): (0.5-3). Thus, a positive electrode slurry with a proper ratio of conductive agent, lithium transition metal composite oxide and binder can be obtained. For example, specifically, the weight ratio of lithium transition metal composite oxide to conductive agent and binder in the positive electrode slurry can be 97:1.4:1.6.

[0059] The composition and morphology of the lithium transition metal composite oxide have been described in detail above and will not be repeated here. Those skilled in the art can select appropriate lithium transition metal composite oxides according to the specific performance requirements of the positive electrode. The specific type of the conductive agent is not particularly limited, for example, it can be conductive carbon black, graphene, etc. The binder can be, but is not limited to, polyvinylidene fluoride, etc.

[0060] S200: coating the positive electrode slurry on the surface of the current collector

[0061] According to some examples of the present application, in this step, the positive electrode slurry formed previously can be coated on the surface of the current collector. The specific parameters and methods of coating the positive electrode slurry are not particularly limited, as long as the positive electrode slurry can be evenly coated on the surface of one side of the current collector.

[0062] S300: cold pressing the current collector having the positive electrode slurry

[0063] According to some examples of the present application, in this step, the current collector with the positive electrode slurry is cold pressed. Specifically, the cold pressing process can be performed at a pressure of 30-40 tons, a cold pressing rate of 3-4 meters / minute, and a compaction density of 4.05-4.25 g / cm 3 .

[0064] Thus, a positive electrode can be obtained in which the average particle size Dp of the lithium transition metal composite oxide in the direction parallel to the plane where the current collector is located and the average particle size Dv of the lithium transition metal composite oxide in the direction perpendicular to the plane where the current collector is located meet the above conditions. The positive electrode has all the characteristics and advantages of the above-mentioned positive electrode, which will not be repeated here. In general, the positive electrode obtained by this method can have good cycle performance.

[0065] The inventors have found that by adjusting the value of the pressure, the cold pressing rate and the cold pressing density in the cold pressing process, the lithium transition metal composite oxide with a suitable particle shape can be controlled to be evenly distributed on the surface of the current collector in a certain orientation. In this way, the morphology of the lithium transition metal composite oxide can be kept from being damaged by the cold pressing process, and the arrangement of the dominant crystal plane and the non-dominant crystal plane in the lithium transition metal composite oxide on the surface of the current collector can be adjusted, thereby obtaining a positive electrode with good cycle performance and electrical performance.

[0066] According to some examples of the present application, after the positive electrode slurry is coated on the surface of the current collector, before the cold pressing process, the positive electrode slurry on the surface of the current collector may be further dried. The specific parameters of the drying process are not particularly limited, and those skilled in the art may select the parameters and methods of the drying process according to actual conditions to obtain a slurry layer with uniform thickness.

[0067] After the cold pressing process, the current collector can be further cut to obtain a positive electrode of appropriate size.

[0068] According to some examples of the present application, the negative electrode of the electrochemical device may further have an additive. Thus, it further includes an operation of covering the surface of the negative electrode active material layer with the additive. Specifically, the additive can be formed on the negative electrode active material layer by rolling. For example, the negative electrode with the additive can be rolled at a speed of 0.5-2 m / s under a pressure of 5-30 tons. According to some examples of the present application, the additive may include at least one of lithium powder, lithium strip, and lithium-containing compound. Thus, the quality of the electrochemical device obtained by the method can be further improved.

[0069] Example

[0070] Preparation of positive electrode sheet: The positive electrode material obtained in the following example, conductive carbon black, and binder polyvinylidene fluoride are mixed in a weight ratio of 97:1.5:1.5 in an N-methylpyrrolidone (NMP) solvent system to form a positive electrode slurry. Aluminum foil is used as the current collector, and the positive electrode slurry is coated on the current collector with a coating weight of 17.2 mg / cm 2 After drying, cold pressing and cutting, the positive electrode sheet is obtained.

[0071] Preparation of negative electrode sheet: The current collector uses copper foil, the negative electrode active material uses artificial graphite, and the binder uses styrene-butadiene rubber and sodium carboxymethyl cellulose; artificial graphite, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a weight ratio of 96:2:2 and dispersed in deionized water to form a slurry, which is then evenly stirred and coated on the copper foil, dried to form a negative electrode active material layer, and cold pressed to obtain a negative electrode sheet. Some embodiments further add a single lithium strip on the surface of the negative electrode active material layer, with an addition amount of 2.5 mg / cm 2 , cold pressed to obtain a negative electrode sheet containing additives.

[0072] Preparation of isolation membrane: A polyethylene porous polymer membrane with a thickness of 8 μm was used.

[0073] Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate (1.15 mol / L) and a non-aqueous organic solvent (ethylene carbonate (EC): propylene carbonate (PC): diethyl carbonate (DEC) = 1:1:1, weight ratio) are mixed to obtain an electrolyte.

[0074] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, shaping, etc.

[0075] Observation method of negative electrode texture: After the lithium-ion battery is fully charged, discharge it to 3.0V, disassemble it in a dry room or glove box, spread the negative electrode flat and take a clear picture with a suitable magnification with a camera to observe whether there are stripes on the surface of the negative electrode.

[0076] Cyclic performance test method: the temperature is 25℃, the charging process is 0.7C constant current charging to 4.6V, constant voltage to cut-off current 0.025C, and then 0.5C discharge to 3.0V. The first cycle discharge capacity is 100%, and the capacity retention rate of the lithium-ion battery after 200 cycles is recorded.

[0077] X-ray powder diffraction test method: adjust the lithium-ion battery to the corresponding voltage at a current density of 10mA / s, and after standing for 5 minutes, disassemble it in a glove box or dry room. Select the center of the positive electrode and cut it into a 3×3cm piece. Characterize it on a Bruker X-ray powder diffractometer, collect diffraction peaks in the range of 10-80°, and the collection speed is 1° per minute.

[0078] The test method for Dp and Dv is as follows: Take the positive electrode sheet and process it with a slicer to obtain a cross section perpendicular to the surface of the current collector. The diameter of the particles in the cross section is measured in the direction parallel to the plane of the current collector and perpendicular to the plane of the current collector and the size is recorded. The diameter refers to the maximum length of the particle in the defined direction. The statistical method is to select particles from left to right and from top to bottom, and the statistical number of the average particle size is 100 particles.

[0079] Example 1

[0080] Cobalt nitrate and aluminum nitrate are mixed in a molar ratio of Co:Al=99:1 and dissolved in 5 times the mass of deionized water. Sodium carbonate and ammonia water are added to adjust the pH of the system to 8.2, and stirred thoroughly for 24 hours to obtain a precipitate. 0.5% of the mass of the precipitate as an additive ammonium oxalate is added to the precipitate, mixed evenly, and sintered at 800°C for 24 hours to obtain a precursor. The precursor is mixed evenly with sodium carbonate at a Co:Na chemical dosage ratio of 0.99:0.75, and reacted at 800°C for 36 hours to obtain a powder material. After fully grinding it for 3 hours, it is mixed evenly with lithium nitrate at a molar ratio of Na:Li=1:5, and reacted at 250°C for 8 hours. The reaction product is washed with deionized water for more than 5 times, and then the powder is dried to obtain the positive electrode material Li 0.73 Na 0.01 Co 0.99 Al 0.01 O2. Li 0.73 Na 0.01 Co 0.99 Al 0.01 The O2 positive electrode material powder was mixed with conductive carbon and binder in a weight ratio of 97:1.5:1.5 and NMP to form a slurry, which was coated on the surface of the Al current collector and dried in an oven at 120°C for 2 hours until dry. It was then cold pressed at a pressure of 35 tons at a rate of 3.5 m / min and a density of 4.15 g / cm 3 After cutting, the positive electrode sheet is obtained.

[0081] Additive single-element lithium strip is set on the surface of the negative electrode active material layer, with an addition amount of 2.5 mg / cm 2 , and a negative electrode sheet with additives is obtained by rolling.

[0082] Example 2

[0083] Cobalt nitrate and titanium nitrate were mixed and dissolved in 5 times the mass of deionized water according to Co:Ti=95:5, sodium carbonate and ammonia water were added to adjust the pH of the system to 6.5, and the mixture was stirred for 12 hours to obtain a precipitate. 0.5% of the mass of the precipitate as an additive sodium bicarbonate was added to the precipitate, mixed evenly, and sintered at 750°C for 24 hours to obtain a precursor. The precursor was mixed evenly with sodium carbonate at a Co:Na chemical dosage ratio of 0.95:0.76, and reacted at 800°C for 36 hours to obtain a powder material. After fully grinding it for 3 hours, it was mixed evenly with lithium nitrate at Na:Li=1:5, and reacted at 250°C for 8 hours. The reaction product was washed with deionized water for more than 5 times, and then the powder was dried to obtain the positive electrode material Li 0.74 Na 0.01 Co 0.95 Ti 0.05 O2.

[0084] The slurry, cold pressing parameters and additives are the same as those in Example 1.

[0085] Example 3: The preparation method is consistent with that of Example 1, except that the pH of the system is adjusted to 8.7 and stirred for 24 hours; the precursor is sintered at 900°C for 36 hours to obtain the positive electrode material Li 0.73 Na 0.01 Co 0.99 Al 0.01 O2.

[0086] Example 4: The preparation method is consistent with that of Example 2, except that sodium carbonate and ammonia water are added to adjust the pH of the system to 8.5, and the mixture is stirred for 24 hours, and sintered at 950° C. for 48 hours to obtain a precursor.

[0087] Example 5: The preparation method is the same as that of Example 1, except that the precursor is mixed with sodium carbonate and reacted at 850°C for 24 hours to obtain a powder material. After being fully ground for 3 hours, it is mixed with lithium nitrate at a molar ratio of Na:Li=1:5 and reacted at 450°C for 12 hours. The cold pressing process is carried out at a pressure of 36 tons, the cold pressing rate is 3 meters / minute, and the compaction is controlled at 4.16g / cm 3 .

[0088] Example 6: The preparation method is consistent with that of Example 1, except that the negative electrode plate is not modified with additives.

[0089] Example 7: The preparation method is consistent with that of Example 1, except that the precursor is obtained by reacting at 950°C for 48 hours.

[0090] Example 8: Li with R-3m space group structure 0.7CoO2 was used as the positive electrode material. The slurry and cold pressing parameters were the same as those in Example 1. The negative electrode sheet was not modified with additives.

[0091] Example 9: Li with R-3m space group structure 0.75 Co 0.86 Mg 0.14 O2 was used as the positive electrode material. The slurry and cold pressing parameters were the same as those in Example 1. The negative electrode sheet was not modified with additives.

[0092] Example 10: Li with R-3m space group structure 0.99 Co 0.99 Al 0.01 O2 is used as the positive electrode material. The slurry and cold pressing parameters are the same as those in Example 1, and the negative electrode sheet is not modified with additives.

[0093] Comparative Example 1

[0094] Cobalt nitrate and aluminum nitrate are mixed and dissolved in 5 times the mass of deionized water according to Co:Al=99:1, sodium carbonate and ammonia water are added to adjust the pH of the system to 9.8, and it is fully stirred for 36 hours to obtain a precipitate. Add 0.5% of the mass of the precipitate as an additive ammonium oxalate to the precipitate, mix evenly, and sinter at 600°C for 24 hours to obtain a precursor. After the precursor is evenly mixed with sodium carbonate at a Co:Na chemical dosage ratio of 0.99:0.77, react at 1000°C for 36 hours to obtain a powder material. After fully grinding it for 3 hours, mix it evenly with lithium nitrate at Na:Li=1:5, and react at 600°C for 8 hours. The reaction product is washed with deionized water for more than 5 times, and then the powder is dried to obtain the positive electrode material Li 0.76 Na 0.01 Co 0.99 Al 0.01 O2.

[0095] The slurry and cold pressing parameters are the same as those in Example 1. The negative electrode sheet is not modified with additives.

[0096] Comparative Example 2: The preparation method is the same as that of Comparative Example 1, except that sodium hydroxide is added to adjust the pH of the system to 11.8.

[0097] Comparative Example 3: The preparation method is the same as that of Comparative Example 1, except that the precursor is sintered at 1000° C. for 24 hours, and the powder material is reacted at 1050° C. for 24 hours. The negative electrode sheet is not modified with additives.

[0098] Comparative Example 4: The preparation method is the same as that of Example 8, except that: Li 0.88 CoO2 was used as the positive electrode material.

[0099] Comparative Example 5: The preparation method is the same as that of Example 1, except that the cold pressing is performed under a pressure of 65 tons, the cold pressing rate is 6 m / min, and the compaction is 4.29 g / cm 3 The negative electrode plate is not modified with additives.

[0100] Comparative Example 6: The preparation method is the same as that of Example 10, but the difference is that Li with R-3m space group structure and D1 of 6.4 μm and D2 of 4.6 μm is used. 0.99 Co 0.99 Al 0.01 O2 is used as the positive electrode material. Cold pressing density is 3.94g / cm 3 .

[0101] X-ray powder diffraction test was performed on Example 1 and Comparative Example 1. Figure 5 as well as Figure 6 It can be seen that at the corresponding voltages (4.6 V and 3.0 V), the broadening and peak shift of the characteristic peak of Example 1 are smaller than those of Comparative Example 1. Figure 7 and Figure 8 It can be seen that the surface of Comparative Example 1 does not have the twisted streaks that appeared in Example 1. Fig. 9 It can be seen that the cycle capacity retention rate of Comparative Example 1 is greatly reduced. The test results of the above embodiments and comparative examples are shown in Table 1 below, where Y indicates the presence of negative electrode lines, and N indicates the absence of negative electrode lines.

[0102] Table 1

[0103]

[0104] As shown in Table 1, whether it is the positive electrode material of P63mc or R-3m structure, the embodiments with Dp / Dv within the range defined in this application all have good cycle performance, which is better than the comparative example. And as shown in Examples 1 to 10, (Dp+Dv) / 2D N50 In the range of 0.8 to 1.25, it can have a more excellent cycle stability. By comparing Example 1 with Example 6, it can be seen that the positive electrode material of the P63mc structure is supplemented with lithium by using additives, which can further improve its cycle stability.

[0105] In addition, it can be seen from Comparative Examples 1 and 5 that when the ratio D1 / D2 of the average long-axis particle size D1 to the average short-axis particle size D2 of the positive electrode material is too small and / or the cold pressing conditions are not suitable, it is difficult to achieve the Dp / Dv specified in the present application, and its cycle stability is correspondingly poor.

[0106] X-ray powder diffraction tests were performed on samples of some embodiments and comparative examples. The test results are shown in Table 2 below:

[0107] Table 2

[0108] I1 I2 I3 I1 / I3 4.6V cycle 200 times retention rate Example 1 1.01 0.4 1.0 1.01 78.9% Example 7 1.42 0.64 1.73 0.82 70.4% Comparative Example 1 0.41 0.09 1.46 0.28 47.3%

[0109] As shown in Table 2 above, I1 / I3 of Comparative Example 1 is less than 0.8, indicating that there is a risk of pulverization under high voltage. Therefore, the cycle retention rate of Comparative Example 1 is also significantly lower than that of the embodiment.

[0110] After 8 cycles, the I2 / I3 change rate, peak shift and half peak width change rate of X-ray powder diffraction were tested. The test results are shown in Table 3 below:

[0111] Table 3

[0112]

[0113] As shown in Table 3, Examples 1, 8 and 9 all have smaller peak shifts, and the I2 / I3 change rate and half peak width change rate are also significantly smaller than those of Comparative Example 4, indicating better stability. The 4.6V cycle retention rate after 200 cycles also confirms the above view.

[0114] The above description is only an example of the present application and does not constitute any form of limitation to the present application. Although the present application is disclosed as above with a preferred embodiment, it is not intended to limit the present application. Any technician familiar with the present profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution of the present application.

Claims

1. A positive electrode, comprising: A positive electrode active material layer located on a current collector; The positive electrode active material layer contains a lithium transition metal composite oxide; The average particle size of the lithium transition metal composite oxide in the direction parallel to the plane where the current collector is located is Dp, and the average particle size of the lithium transition metal composite oxide in the direction perpendicular to the plane where the current collector is located is Dv, satisfying: 1.1 ≤ Dp / Dv ≤ 2.

3. Here, Dv and Dp are the average diameters of the particles. The test method for the average diameter is to randomly select 1 position of the positive electrode, process it with a slicing machine to obtain a cross-section perpendicular to the surface of the current collector. For the particles in the cross-section, measure their diameters in the directions parallel to and perpendicular to the plane where the current collector is located and record the sizes. The diameter refers to the maximum length of the particle in the defined direction, and the statistical method is to select particles in the order from left to right and from top to bottom. The statistical quantity of the average particle size is 100 particles; The lithium transition metal composite oxide has a long-axis average particle size D1 and a short-axis average particle size D2, satisfying: 1.4 ≤ (D1 / D2) ≤ 5.5; The lithium transition metal composite oxide satisfies: 5 μm ≤ Dp ≤ 25 μm.

2. The positive electrode according to claim 1, wherein the lithium transition metal composite oxide satisfies: 0.8≤(Dp+Dv) / 2D N50 ≤1.25, where D N50 is the median particle size of the lithium transition metal composite oxide.

3. The positive electrode according to claim 1, satisfying at least one of the following conditions: a) the lithium transition metal composite oxide has an R-3m space group structure; the lithium transition metal composite oxide includes Li x1 Ni y1 Co z1 Mn k Z q O b-a T a ,in, Z includes at least one of B, Mg, Al, Si, P, S, Ti, Cr, Fe, Cu, Zn, Ga, Y, Zr, Mo, Ag, W, In, Sn, Pb, Sb, and Ce, T is a halogen, and x1, y1, z1, k, q, a, and b respectively satisfy: 0.2 < x1 ≤ 1.2, 0 ≤ y1 ≤ 1, 0 ≤ z1 ≤ 1, 0 ≤ k ≤ 1, 0 ≤ q ≤ 1, 1 ≤ b ≤ 2, and 0 ≤ a ≤ 1; b) The lithium transition metal composite oxide has a P63mc space group structure; the lithium transition metal composite oxide includes Li x2 Na z2 Co 1-y2 M y2 O 2±n X n , where 0.6 < x2 < 0.95, 0 ≤ y2 < 0.15, 0 ≤ z2 < 0.03, 0 ≤ n ≤ 0.2, where M includes at least one of Al, Mg, Ti, Mn, Fe, Ni, Zn, Cu, Nb, Cr, and Zr, and X is a halogen.

4. The positive electrode according to claim 1, wherein the lithium transition metal composite oxide satisfies: 7 μm ≤ D1 ≤ 28 μm.

5. The positive electrode according to claim 1, when the electrochemical device including the positive electrode is charged to a voltage of 4.6V, the positive electrode satisfies: The X-ray diffraction spectrum has at least characteristic peak P1 and characteristic peak P2 in the range of 17° to 20°, and the peak intensity I1 of P1 is greater than the peak intensity I2 of P2; Moreover, when the electrochemical device is discharged to a voltage of 3.0V, the positive electrode satisfies: The X-ray diffraction spectrum has a characteristic peak P3 in the range of 17° to 20°, and the peak intensity I3 of P3 satisfies: (I1 - I2) ≤ I3 ≤ (I1 + I2).

6. The positive electrode according to claim 5, the ratio I1 / I3 of the peak intensity I1 of P1 and the peak intensity I3 of P3 is not less than 0.

8.

7. The positive electrode according to claim 1, wherein The positive electrode satisfies: when an electrochemical device including the positive electrode is subjected to 8 charge and discharge cycles in the range of 3.0V to 4.6V and discharged to a voltage of 3.0V, the peak position offset of the highest peak in the X-ray diffraction spectrum of the positive electrode after the cycle is no more than 0.1° compared with the positive electrode before the cycle; and the half-peak width change rate of the highest peak is less than 5%. 8 . An electrochemical device comprising a positive electrode, a negative electrode, and a separator, wherein the positive electrode is the positive electrode according to claim 1 . 9 . The electrochemical device according to claim 8 , wherein the negative electrode has stripes on its surface when discharged to a voltage of 3.0 V.

10. An electronic device comprising the electrochemical device according to any one of claims 8 to 9.

Citation Information

Patent Citations

  • Electrode for battery, nonaqueous electrolyte battery, and battery pack

    CN103000871A

  • Nickel composite hydroxide and method for producing the same, positive electrode active material and method for producing the same as well as nonaqueous electrolytic secondary cell

    CN103915618A